Doing qualitative research : a practical handbook - Silverman, David (Sage Publications, 2005)
"This step-by-step guide provides answers to all the questions students ask when beginning their first research project. Silverman demonstrates how to learn the craft of qualitative research by applying knowledge about different methods to actual data. He provides practical advice on key issues, such as: defining `originality' and narrowing down a topic; keeping a research diary and writing a research report; and presenting research to different audiences."--The publisher